Determining diet and establishing a captive population of a rare endemic detritivore, the endangered Novisuccinea chittenangoensis (Pilsbry, 1908) (Pulmonata: Succineidae). (15th December 2018) - Gilbertson, Cody R; Rundell, Rebecca J; Niver, Robyn
Abstract: Land snails, particularly rare or narrow-range endemic species, are among the most threatened animals on Earth. For such species, captive-breeding programmes may be important for ensuring backup populations or for supplementing wild populations. However, establishing such programmes can be difficult, because natural history information on rare species is often scarce, and there are few potential 'model' captive-breeding programmes. Captive breeding is further complicated by wild diets that are poorly known and difficult to replicate. Furthermore, small populations can lead to official restrictions or reluctance to undertake dietary experimentation. Here we demonstrate how close captive observation of the target threatened species, combined with dietary experimentation and behavioural observation on a non-endangered but ecologically similar surrogate species, is an effective approach for determining the optimal captive diet. In order to establish a captive colony of the Chittenango ovate amber snail Novisuccinea chittenangoensis, which is known from only one side of a single waterfall in central New York State, we first performed dietary experiments on a common co-occurring succineid. This surrogate species grew and reproduced significantly better on certain types of leaf litter than on other diets. After failed initial attempts at raising N. chittenangoensis, we assessed leaf litter preferences and growth of a single captive N. chittenangoensis . This single-snail approach allowed us to gain information quickly with no impact on the wild population. Additional wild N. chittenangoensis were then brought into captivity for breeding and fine-tuning of the leaf-litter diet. Captive N. chittenangoensis thrived on the successful diet, which ultimately resulted in 632 F1 offspring with 0% mortality (compared with 80% mortality and significantly lower growth rate experienced in previous studies of N. chittenangoensis ), some of which were released into the wild.